A COMPARISON OF THE ENFORCEMENT OF CEDAW AND CRC IN MALAYSIA AND INDONESIA - Angel Damayanti (Sociae Polites, 2014)
Abstract: All ASEAN member States have ratified and acceded the Convention on the Elimination of AllForms of Discrimination against Women (CEDAW) and the Convention on the Rights of the Child (CRC).As parties of both conventions, Malaysia and Indonesia should enforce specific mechanism and rules inline with CEDAW and CRC norms and standards. Yet, both countries ask reservation for severalsubstantive and procedural matters on both conventions. This certainly restricts the enforcement on theelimination of all forms of discrimination against women and the protection of the rights of children. Thisis in addition to the Islamic shariah implemented in Malaysia and some regions in Indonesia as well asstereotype of women and men regarding their role in economic, social, and political. This paper willessentially show some hindrances for both governments and therefore should take some steps to reducethe limitation. The analysis will be delivered by examining all reports given by both governments to UNCommission on Women and Children, as well as shadow reports from NGOs.Keywords: CEDAW, CRC, Reservation, Radical Feminism Abstrak: Semua Negara anggota ASEAN (Association of Southeast Asia Nation) telah meratifikasi danmengaksesi Konvensi tentang Penghapusan Segala Bentuk Diskriminasi terhadap Perempuan(Convention on the Elimination of All Forms of Discrimination against Women - CEDAW) dan Konvensitentang Hak-hak Anak (Convention on the Rights of the Child - CRC). Sebagai pihak yang meratifikasikedua konvensi tersebut, Malaysia dan Indonesia tentu saja harus tunduk dan mengikuti aturan yangtertera di dalam konvensi tersebut. Sayangnya, Malaysia dan Indonesia mengajukan reservasi terhadapbeberapa aturan dalam konvensi, baik secara substansi maupun prosedur. Hal ini tentu sajamenghambat penghormatan dan pelaksanaan kedua konvensi secara menyeluruh. Hal ini semakindipersulit dengan adanya hukum Islam yang berlaku di Malaysia dan beberapa daerah di Indonesia sertastereotipe mengenai perbedaan peran laki-laki dan perempuan yang diterapkan di dalam masyarakatkedua Negara. Paper ini akan menunjukkan beberapa kendala yang dihadapi oleh pemerintah keduaNegara dalam menerapkan aturan-aturan CEDAW dan CRC secara menyeluruh. Hal ini akan dilakukandengan menganalisa laporan-laporan tertulis yang telah dibuat oleh pemerintah dan NGO keduaNegara.Kata Kunci: CEDAW, CRC, Reservasi, Feminisme Radikal